2004
DOI: 10.1093/oxfordjournals.schbul.a007098
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Mental Illness Stigma

Abstract: The effectiveness of efforts designed to address mental illness stigma will rest on our ability to understand stigma processes, the factors that produce and sustain such processes, and the mechanisms that lead from stigmatization to harmful consequences. Critical to such an understanding is our capacity to observe and measure the essential components of stigma processes. This article is designed to assist researchers in selecting or creating measures that can address critical research questions regarding stigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
970
2
28

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,113 publications
(1,025 citation statements)
references
References 177 publications
(191 reference statements)
25
970
2
28
Order By: Relevance
“…Previous research suggests that those with personal history of mental illness might be expected to have less negative attitudes towards mental illness (Bell et al 2006;Kobau et al 2009;Link et al 2004), and therefore that the effect of the documentary would be attenuated in this population. Despite this however, we found significant positive changes in attitude toward mental illness in response to the documentary.…”
Section: Limitationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous research suggests that those with personal history of mental illness might be expected to have less negative attitudes towards mental illness (Bell et al 2006;Kobau et al 2009;Link et al 2004), and therefore that the effect of the documentary would be attenuated in this population. Despite this however, we found significant positive changes in attitude toward mental illness in response to the documentary.…”
Section: Limitationsmentioning
confidence: 87%
“…Mental illnesses are amongst the conditions that are most profoundly affected by disease-associated stigma -indeed, it has been suggested that for some affected individuals, the effects of mental illness-related stigma are so negative that they actually often outweigh the negative effects of the illness itself (Hinshaw and Stier 2008). Stigma is a complex social construct comprising interrelated processes that operate at the level of institutions (institutional stigma), social groups (public stigma), and the individual (internalized or self-stigma) (Corrigan and Watson 2002;Hinshaw and Stier, 2008;Lauber and Rossler 2007;Link et al 2004). Of the three levels at which stigma operates, public stigma (defined as the phenomenon whereby large social groups have negative attitudes towards and beliefs about, and even act against those with a disenfranchised trait -like mental illness (Corrigan and Watson 2002)) has received the greatest attention.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increasing size of the U.S. Latino population, the relatively common occurrence of major depression, and the significant treatment-seeking barriers posed by stigma, more research on this topic among Latinos is needed (13). Stigma research in the Latino culture requires adequate measures for key stigma constructs in order to investigate processes by which stigma beliefs deter treatment utilization (4). Concerns about the cultural and linguistic appropriateness of measures underscore the need to ensure that adequate stigma measures are available for Latinos.…”
mentioning
confidence: 99%
“…It is plausible that the language used in the implicit test could reflect benevolent paternalism rather than an increase in positive attitudes (Link, 2004). As such, researchers should be aware that IRAP effects might depend on the stimuli employed to instantiate target and attribute concepts (De Houwer, 2002).…”
Section: Discussionmentioning
confidence: 99%